INTRODUCTION AND APPLICATION OF MODERN ANALYTICAL INSTRUMENS IN LABORATORIES - Yelfi Anwar (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2026)
The development of laboratory technology requires a deep understanding of modern analytical instruments suchas UV-Vis Spectrophotometer, HPLC, and GC-MS. However, many prospective laboratory technicians, especiallyvocational students, still have limited literacy regarding the working principles and applications of theseinstruments. This community service activity aims to improve the knowledge of students at SMK Tanjung Priok 1North Jakarta through an interactive webinar method. The implementation method includes presenting materialon instrument working principles, main components, data interpretation, and interactive discussion sessions. Thesuccess of the activity was measured through pre-test and post-test instruments analyzed descriptively. Theevaluation results showed a significant increase in participant understanding. The results showed an increase inthe average score from 80.83 in the pre-test to 95.83 in the post-test, with an improvement of 15.0 points. Thisimprovement proves that webinar-based education is effective in broadening participants' technical insightsregarding modern analytical instruments in the laboratory.